Diffusion of deformable nanoparticles in adhesive polymeric gels. (October 2022) - Yu, Siqin; Tian, Falin; Shi, Xinghua
Abstract: Deformable nanoparticles (DNPs) such as liposomes are widely used to load and deliver drugs across hydrogel-like biological barriers such as mucus and tumor interstitial matrix. The rigidity of DNPs is found to have a huge effect on their diffusivity in biological gels, while the underlying mechanism is still unclear. Here, we propose a theoretical model to describe the diffusion behavior of DNPs in biological hydrogel and elucidate the mechanism by which the stiffness of DNPs affects their diffusion properties through decoupling their deformation and transportation during diffusion. By considering three physical parameters, including the stiffness of DNPs, the mesh size of the polymer network and the adhesion property of the hydrogel, we find that both stiffness and adhesion play critical roles in the diffusion of DNPs. In addition, there is an optimal diffusivity when the stiffness and adhesion are balanced. The phase diagram of DNPs with different stiffness and optimal diffusivity in the plane of mesh size and adhesion strength is further obtained through systematic calculations. The prediction is highly consistent with recent experimental and molecular simulation findings for the diffusion of liposomes of varying stiffness in gastrointestinal mucus. By elucidating the mechanism by which stiffness affects the diffusion of DNPs in physiological gels, our model could provide a rationale for designing drug carriers with enhanced diffusion capacity in biological hydrogels.